Fabula és história határán: két festői történet a XVI. század Magyarországáról - Máté, Ágnes (Antikvitás & Reneszánsz, 2018)
The paper discusses two anecdotes concerning the Hungarian court. The first anecdote is transmitted by Le Vite of Giorgio Vasari on Visino, a Florentine painter, and his adventure in the court of Louis II. The big-mouth Florentine almost lost his life because the Hungarian aristocrats misunderstood his communicating of cultural preferences for Tuscany in comaprison to Buda court. The other text is a short narrative taken from the Le Sei Giornate of Sebastiano Erizzo. Erizzo's story tells about King John Szapolyai and one of his servants who stole a precious ring from his master. The servant accuses a painter of the sin and almost makes him killed for something the painter did not commit. The King, conscious about his servant's deed frees the painter and punishes the servant by sending him away from his service and giving him the same ring the servant risked his own position and another person's life for. My analysis discusses the possible historical and cultural background of the two stories. It also calls attention to the psychological effects they may have caused in their contemporary readers and the different reading strategies we approach them after the Enlightment of European culture.